Extraction and partial purification of proanthocyanidins (PAC) from Cacao seeds - Simogan, Jerry Jr. Parparan (2011)
Extraction from fresh cacao seeds was carried out using 25%, 50%, 70%, and 95%n ethanol to determine what concentration gives the highest yield in extracting proanhocyanidins (PAC). The trend showed that as ethanol concentration increased, the yield also increased (25%=20.67%, 50%-50.80%, 70%-58.47% and 95%=80.20% of the entire PAC content of cacao seeds). The 95% EtOH, which yielded the highest, was then used for assessing efficiency of extraction protocol employed. The triple extraction test showed that single extraction is enough to extract majority of the PAC of the cacao seed powder and that 95% EtOH is far better solvent than hot water to extract PAC. The 95% EtOH was used for extracting crude PAC which was purified alter using Diaion HP-20 resin chromatographic column. There was a total yield from the water and 10% EtOH washing of 38.519% monitored through OD 280 scanning, which constitutes the contaminants removed from the extract. Proanthocyanidins were eluted using 70% ethanol. The chromatographic procedure using the Diaion enriched the PAC content per unit absorbance at 280 nm (OD280) of the crude extract 1.62 fold; thus, a partially purified PAC extract was obtained. There was an excellent recovery of the PAC content of the crude extract and no loss was recorded after purification.
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2011
Keywords: Proanthocyanidins; Extraction; 95% ethanol; Purification by Dia-ion HP20.; Cacao seeds; PAC (Proanthocynidins); Crude extract